Polytherapy in the management of epilepsy - Samekto Wibowo, Samekto Wibowo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Antiepileptic drugs take a dominant role in the management of epilepsy. Although monotherapy has been recommended, polytherapy sometimes is very difficult to be avoided. This study wanted to remind: what factors should be considered in epilepsy polytherapy. Drug-drug interactions and the risk of side effects might occures. Optimal polytherapy was often achieved with drugs that had different mechanism of action, relatively few side effects, high therapeutic indexes, and limited or no drug interactions. To choose the drug groups, the following factors should also be considered, namely: efficacy, safety, suitability and cost of treatment. In short, polytherapy should be rational.Key words: epilepsy - monotherapy - polytherapy - rational use of drugs - drugs infraction